2001
DOI: 10.1507/endocrj.48.685
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Serum Testosterone Levels, Body Fat and Muscle Mass Distribution in Women with Polycystic Ovary Syndrome.

Abstract: Abstract.We investigated the relationships among serum testosterone levels, body fat and muscle mass distribution in women with polycystic ovary syndrome (PCOS).Subjects were 67 women with PCOS (mean age±standard deviation, 28.8±6.6 years). Baseline characteristics included age and height. Trunk-leg fat ratio and trunk-leg muscle ratio were assessed with dual-energy x-ray absorptiometry.Serum testosterone and dehydroepiandrosterone sulfate levels were measured with radioimmunoassays. Relationships among serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Several studies found that greater obesity in the central region as determined by waist circumference, visceral fat, or the central/peripheral fat ratio was associated with lower SHBG levels (171,173,189). Some studies found that a higher trunk/leg fat ratio or upper/lower region fat ratio is associated with higher levels of T (181,190). The effect of fat distribution on hirsutism is unclear.…”
Section: Obesity In Pcos: Cause or Resultsmentioning
confidence: 99%
“…Several studies found that greater obesity in the central region as determined by waist circumference, visceral fat, or the central/peripheral fat ratio was associated with lower SHBG levels (171,173,189). Some studies found that a higher trunk/leg fat ratio or upper/lower region fat ratio is associated with higher levels of T (181,190). The effect of fat distribution on hirsutism is unclear.…”
Section: Obesity In Pcos: Cause or Resultsmentioning
confidence: 99%
“…Indeed, treatment with dihydrotestosterone -the major active metabolite of T -suppressed LPL activity and inhibited adipogenesis in adipocyte cultures derived from abdominal VAT and gluteofemoral SCAT depots of both men and women (albeit to a greater extent in men) (80). It is important to state that T regulates adiposity in women as well, as evidenced by studies of women with polycystic ovary syndrome (PCOS), in which they present elevated levels of T and tend to accumulate more fat in the VAT (82).…”
Section: Testosterone and Body Fat Distributionmentioning
confidence: 99%
“…Testosterone levels and FAI were higher in the classic PCOS phenotype, although no signifi cant association was found between androgens and lean mass. Even though androgens are known to increase muscle mass and strength [ 40 ] and contribute to peripheral muscle mass distribution [ 15 ] , these steroids seem to have a limited eff ect on lean muscle mass in PCOS women [ 17 ] . In turn, while it is known that exercise enhances the amount and strength of lean mass [ 41 , 42 ] , the increase in lean mass seen in our classic PCOS group cannot be explained by the level of physical activity, since this variable was controlled through the assessment of habitual physical activity.…”
mentioning
confidence: 99%